Siyasah Fikih Thinking in the Context of Religious Freedom And Human Rights - Safitri, Delfi; Fikriana, Askana; Maharani, Sri; Ramadhani, Fitria (International Journal of Education, Information Technology, and Others, 2023)
Religious freedom is given to every human being to adhere to their own beliefs and religion. Religious freedom in Indonesia upholds human rights which are regulated in the 1945 constitution. The law on religious freedom acts as a material to protect the entire community and acts of discrimination, religious-based violence, exploitation, and limits of religious authority in religion. Religion is a system that regulates belief and worship in the Almighty God as well as rules related to culture, and a worldview that connects humans to the order of life. Every religion has rules and regulations for life in society. People who have religion will definitely understand more about how to live life. As with human rights, governments must be fair to their people. According to Siyasah Fiqh, religious freedom is prohibited and is an act of coercion that can lead to violations of freedom and human rights. There is no sense in choosing people according to class. The method used for this research is a qualitative approach, namely by collecting data and using information related to the problems in this research. The nature of this research is descriptive analysis. The data source is secondary data. Because there are still many people who change religions without paying attention to the future consequences and many people's rights are lost by not implementing justice.